PENGARUH TERAPI NATURE SOUND TERHADAP TINGKAT STRES MAHASISWA PROFESI STIKES HAMZAR LOMBOK TIMUR - Jaya, Ilham; Rosidi, Ahyar (Midwifery And Complementary Care, 2025)
Background: During this process, nursing students are faced with field practice and various reports required by every student in the nursing program. This can trigger various disorders, one of which is stress. Objective:. This study aims to  determine the " Effect of Nature Sound Therpy on Stress Levels in Nursing Students at Hamzar Health College, East Lombok" Methods: This  study was quantitative with a  pre-experimental design, using a one-group pre-test post- test approach. The population in  this study included 24 nursing students at Hamzar Health College, East Lombok. The sample size was 10 students, using simple random sampling. Data analysis used a paired sample t-test. The instrument used was the Depression, Anxiety, and Stress Scale-42 (DASS-42) questionnaire Result: The results of the paired sample t-test obtained a p-value of 0.000. From these results, it can be concluded that there is an "Effect of Nature Sound Therapy on Stress Levels in Nursing Professional Students at Hamzar Health College, East Lombok." Conclusion: From the results of the research conducted, it was found that there was an influence of nature sound therapy on stress levels in nursing profession students at STIKes Hamzar Lombok Timur. Keywords: Nature Sound, Stress, Students